2001
DOI: 10.1108/eum0000000006155
|View full text |Cite
|
Sign up to set email alerts
|

Targeting consumers who are willing to pay more for environmentally friendly products

Abstract: Concerns related to the environment are evident in the increasingly ecologically conscious marketplace. Using various statistical analyses, investigats the demographic, psychological and behavioral profiles of consumers who are willing to pay more for environmentally friendly products. Finds that this segment of consumers were more likely to be females, married and with at least one child living at home. They reported that today's ecological problems are severe, that corporations do not act responsibly toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

109
1,702
17
123

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,261 publications
(2,123 citation statements)
references
References 21 publications
109
1,702
17
123
Order By: Relevance
“…For example, a person who demonstrates a positive attitude towards organic food products is more likely to purchase in organic supermarkets. Laroche et al (2001) has also found that consumers who perceive ecological problems as having severe consequences for the security of the world, are willing to pay more for the consumption of ecological products. Hence, H1: Consumers who perceive that CO2 emissions from air travel create a severe ecological problem are more willing to compensate for these emissions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a person who demonstrates a positive attitude towards organic food products is more likely to purchase in organic supermarkets. Laroche et al (2001) has also found that consumers who perceive ecological problems as having severe consequences for the security of the world, are willing to pay more for the consumption of ecological products. Hence, H1: Consumers who perceive that CO2 emissions from air travel create a severe ecological problem are more willing to compensate for these emissions.…”
mentioning
confidence: 99%
“…When consumers are more aware of the importance of recycling they are more likely to recycle waste. Laroche et al (2001) investigated the demographic, psychological and behavioral profiles of consumers who are willing to pay more for environmentally friendly products. These consumers think that it is important to behave in an ecologically sound way and we therefore expect consumers who find it important to behave pro-environmentally to be more willing to compensate for CO2 emissions from air travel.…”
mentioning
confidence: 99%
“…This could be due to the attitudes such as importance and inconvenience [14]. As outlined by Bernstroem [23], risk understanding might possibly be significant in awareness of electricity saving.…”
Section: "But Anyway Whom Which Aware Of Environmental Problems Havementioning
confidence: 99%
“…However, contrasting to knowledge and behavior, attitudes are the most important predictors of consumers' willingness to pay more for environmental friendly products. It has been reported that two attitudes namely importance and inconvenience have been studied most by researchers [14]. Amyx et al [15] have described the term "importance", with respect to the environment, as the degree to which one expresses concern about ecological issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation